An Analytical Study on Eschatology and Reasoning in the Light of the Qur'an and Hadith: Interpretation of Selected Verses - Taufik Taufik; Muallim Lubis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The study of eschatology and logic in Islam represents a significant and intellectually rich area within the broader discourse of ʿAqidah (Islamic creed) and Islamic philosophy. Eschatology, derived from the Greek word eschatos meaning